Analisis Narasi Najwa Shihab Terkait Komentar Hotman Paris (Kajian Semantik - Susanna Hutabarat (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2018)
The purpose of this study was to analyze the meaning of the narrative presented by Najwa Shihab which received comments from Hotman Paris Hutapea. This research used qualitative descriptive method, because its purpose is to express the meaning of text. The result of this study prove that there is no element of insulting or degrading the good name of the presented by Najwa Shihab as presented by Hotman Paris. The narrative leads to the condition of not received justice from the state related to the case of splashing hard water.